Article 17 of the Directive on Copyright on the Digital Single Market : A continuation of an established fair balance between fundamental rights? - Paara, Kari (My University, 2020)
The Directive on Copyright on the Digital Single Market was approved by the European Parliament in March 2019. Article 17 of the directive presents new stricter obligations for the online content sharing providers, who are best positioned to prevent copyright violations from occurring on their platforms. According to these new obligations the providers must with their best efforts strive to prevent the uploading of copyright infringing material on their platform. Furthermore, the providers are no longer shielded from liability in circumstances where they do not possess actual knowledge of infringing activities. The purpose of this paper is to examine whether the fair balance between competing fundamental rights constructed by the legislator in Article 17 is in line with the established perception of fair balance visible in the case law of the European legal framework. The competing fundamental rights in the context of Article 17 are the freedom of expression and information, freedom to conduct a business and right to intellectual property. This examination of the case law is carried out primarily by discussing the judgments of Court of Justice of the European Union and European Court of Human Rights. The perceived balance between the freedom to conduct a business and the right to intellectual property can be seen falling in line with the previous case law. The content sharing providers have been subject to increasingly stricter measures which have not been deemed unproportioned or violating the essence of a right to conduct a business. Furthermore, the right to conduct a business has been regarded as a fundamental right of less significance in the case law. The relationship between previous case law and Article 17 is less consistent when it comes to the balance between the freedom of expression and information and right to intellectual property. The freedom of information of the users of the services has become a focal point in the case law and the potential protective measures initiated by Article 17 cannot be seen functioning well with this development. Furthermore, depriving the users of their sole mean of accessing information may constitute as a violation of the essence of the right to information. Consequently, the position of the service provider in implementing measures that fulfill the requirement of fair balance becomes more difficult.

Euroopan unionin parlamentti hyväksyi maaliskuussa 2019 direktiivin tekijänoikeudesta digitaalisilla sisämarkkinoilla. Direktiivin artikla 17 tuo aikaisempaa ankarampia velvoitteita verkkosisällönjakopalvelujen tarjoajille, joiden katsotaan parhaiten kykenevän puuttumaan alustoillaan tapahtuviin tekijänoikeusloukkauksiin. Artiklan 17 esittelemien uusien vaatimusten mukaisesti palveluntarjoajien tulee jatkossa parhaansa mukaan pyrkiä estämään tekijänoikeuksia loukkaavan materiaalin päätyminen alustoilleen. Palveluntarjoajat eivät myöskään enää saa suojaa tilanteessa, jossa niillä ei ole ollut tosiasiallista tietoa tekijänoikeuksia loukkaavan materiaalin olemassaolosta alustallaan. Tämän tutkielman tarkoituksena on selvittää, noudattaako Unionin lainsäätäjän artiklassa 17 hahmottelema perusoikeuksien välinen tasapaino aikaisempaa eurooppalaisessa oikeuskäytännössä löydettyä tasapainoa kilpailevien perusoikeuksien välillä. Kilpaileviksi perusoikeuksiksi on artiklan 17 kontekstissa identifioitu sanan- ja tiedonvälityksen vapaus, elinkeinovapaus ja tekijänoikeudet. Tutkielmassa tarkastellaan pääsääntöisesti Euroopan unionin tuomioistuimen sekä Euroopan ihmisoikeustuomioistuimen ratkaisuja, joissa on tasapainoiltu edellä mainittujen perusoikeuksien toteutumisen välillä. Artiklasta 17 havaittavissa olevan perusoikeuksien välisen tasapainon voidaan katsoa noudattavan elinkeinovapauden ja tekijänoikeuksien osalta oikeuskäytännössä kehittynyttä linjaa. Palveluntarjoajat ovat olleet etenevässä määrin tiukkojen vaatimusten kohteena tekijänoikeusloukkauksien ehkäisemiseksi ilman että vaatimusten katsottaisiin olevan tekijänoikeuksien toteutumisen kannalta kohtuuttomia tai loukkaavan elinkeinovapauden ydintä. Elinkeinovapauden on lisäksi oikeuskäytännössä nähty olevan arvoltaan vähäisempi perusoikeus. Linja ei sen sijaan ole yhtä selkeä tarkasteltaessa sanan- ja tiedonvälityksen vapauden sekä tekijänoikeuksien välistä tasapainoa. Verkon käyttäjien tiedonsaantioikeus on noussut oikeuskäytännössä keskeiseen asemaan, eikä artiklan 17 mahdollisesti aiheuttamien suojaustoimien voida katsoa tukevan tätä kehitystä. Lisäksi oikeuskäytännössä on arvioitu, että ainoan mahdollisen tiedonsaantiväylän häviäminen saattaa kajota oikeuden ytimeen, mikä vaikeuttaa entisestään palveluntarjoajien tehtävää perusoikeuksien välisen tasapainon käytännön toteuttajana.
Keywords: fair balance of fundamental rights, fair balance, intellectual property rights, freedom of expression and information, right to conduct a business, directive on copyright